Lived Temporalities Exploring Duration in Guatemala. Empirical and Theoretical Studies - Mahler, Julia (Cultural Studies, 2007)
In contemporary global capitalist culture, time-consciousness becomes more important than self-consciousness. In the realm of lived time, the identity of the self opens up to an encounter with otherness. Insights into the ways in which this dynamic unfolds enable one to affirm human temporalities in their potential difference to the temporalities of global capitalism. The book offers an empirical exploration of lived temporalities on markets, in buses and in traditional subsistence in Guatemala, and a theoretical exploration of these through the philosophy of Gilles Deleuze and inter-relational approaches within psychoanalysis.